Bladder Endometriosis and Endocervicosis: Presentation of 2 Cases with Endoscopic Management and Review of Literature - Javier Fuentes Pastor; Roberto Ballestero Diego; Miguel Ángel Correas Gómez; Eduardo Torres Díez; Alejandro Fernández Flórez; Gerardo Ballesteros Olmos; Jose Luis Gutierrez Baños (Case Reports in Urology)
Urinary tract endometriosis and endocervicosis are an uncommon pathologic finding, with a common embryological origin. We present 2 cases of female patients with bladder mass. The first one was a finding of a nodular formation in the bladder during study of a nonviable foetus and the second was an incidental finding of a neoformation in the fundus of the bladder during the realization of an ultrasound. In both cases, we performed a surgical management with transurethral resection. Histopathological examination revealed a bladder endometrioma in the first case and endocervicosis with associated endometriosis in the second.